(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article examines Ronald Dworkin’s concept of the liberal community as a response to communitarian critiques of liberalism. It argues that political integration should be understood through shared democratic practices and official political institutions rather than through collective moral or cultural conformity. The article emphasizes that individual rights, political equality, and liberal tolerance are compatible with a strong sense of civic responsibility, maintaining that a just political community enhances both democratic legitimacy and the ethical quality of citizens’ lives. This abstract is generated with artificial intelligence.